2021
DOI: 10.3389/fnins.2021.792264
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant Interhemispheric Functional Connectivity in Diabetic Retinopathy Patients

Abstract: Background: Accumulating lines of evidence demonstrated that diabetic retinopathy (DR) patients trigger abnormalities in brain’s functional connectivity (FC), whereas the alterations of interhemispheric coordination pattern occurring in DR are not well understood. Our study was to investigate alterations of interhemispheric coordination in DR patients.Methods: Thirty-four DR individuals (19 males and 15 females: mean age: 52.97 ± 8.35 years) and 37 healthy controls (HCs) (16 males and 21 females; mean age: 53.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our prior research unveiled abnormal functional connections among the visual network (VN), default mode network (DMN), salience network (SN), and sensorimotor network in individuals with DR. 39 Another study demonstrated that interhemispheric coordination among the auditory network, visual network, default mode network, and sensorimotor network is significantly compromised in patients with diabetic retinopathy. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Our prior research unveiled abnormal functional connections among the visual network (VN), default mode network (DMN), salience network (SN), and sensorimotor network in individuals with DR. 39 Another study demonstrated that interhemispheric coordination among the auditory network, visual network, default mode network, and sensorimotor network is significantly compromised in patients with diabetic retinopathy. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Retinopathy is a common diabetes complication, which can lead to visual impairment. Most studies on T2DM patients with optic nerve-related complications have reported negative alterations in the MOG and the precuneus, including decreased synchronous neural activities, decreased dynamic cerebral activity ( Yang et al, 2022 ), lower degree centrality ( Huang et al, 2021 ), and decreased connectivity ( Zhang et al, 2020 ; Wan et al, 2021 ). When extended to a wider population of diabetes, the results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, the FC method needs a prior settlement of seed region, limiting the whole-brain analysis of brain function. Therefore, voxel-wise rs-fMRI indices, manly including amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo) and voxel-mirrored homotopic connectivity (VMHC), have attracted significant research interest in the neural abnormalities of T2DM patients ( Cui et al, 2014 , 2022b ; Zhou et al, 2014 ; Peng et al, 2016 ; Wang et al, 2017 , 2019 , 2020 ; Shi et al, 2020 ; Zhang et al, 2020 ; Wan et al, 2021 ; Liu M. et al, 2022 ). Each of these metrics partly contributed to elucidating the functional abnormalities related diabetes, respectively.…”
Section: Introductionmentioning
confidence: 99%